Study guides

☆☆

Q: 2X Times Square root of X?

Write your answer...

Submit

Related questions

Its the square root of 2 times x Ambiguous. More clear is x times square root of 2

2X

It depends entirely on the value of x.

(√4x^2)(√36x)=2x(6√x)=12x√x

sqrt(XX) - 2x = X - 2X = -X

2 x âˆš3 = 3.464 (rounded)

If it is (x+x)2 then it is (2x)2 and the sqrt of that is 2x.

X = any number you like. You see, in order to solve for x, one would have to know what those two things equaled. For instance, what if x = zero? The square root of 2 times zero multiplied by the square root of 50 times zero, is going to be zero.

The question is ambiguous. Do you mean √(24*x4) or √24*x4? √(3x) or √3*x? The answer to √(24*x4) / √(3x) = (8x3) = 2x*√(2x)

is (x^2)/2=x then (x^2)=2x then x=square root of (2x)

SQRT(X) * SQRT(X) = X

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

200 times the square root of x

2x square root 6x y squared

The square root of 4x^2 is solved by first doing the square root of 4. This is plus or minus two - because -2 x -2=4. The square root of x^2 is x. So the answers are 2x or -2x. If your question was (4x)^2, then the answer would be 4x.

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

As stated, the question does not make sense: x square root of 4 is x2 or 2x, as it is more conventionally written. There is no term for 2x in the expansion of x - 3*sqrt(7)

0

2 times x times x equals 2x2

2x^2=76, x^2=38, x=square root of 38- about 6.17

(2x - i)(2x + i)where i is the square root of negative 1.x = 0.5i, -0.5i

5

x = the square root of -2

If you mean: 2x^2 -5x = 35 then 2x^2 -5x -35 = 0 and by using the quadratic equation formula the value of x is (5-square root 305)/4 or (5+square root 305)/4

It is 5*x^3*y*sqrt(2x)